الشيخ محمد بن سليمان حمداوي وجهوده الدعوية من فترة (1910إلى 1994م) - قحمص, سهيلة; قويدري, خولة (University of eloued جامعة الوادي, 2021)
"حديث أبى الدرداء قال قال رسول الله- صلى الله عليه وسلم- :«إن العلماء وَرثَة الأنبياء». ولقد صار العلماء على هديه واقتفوا أثره واتبعوهُ، رغم كل التحديات التي مرت بها الأمة الإسلامية من حروب ومؤامرات، ومكائد دبرها أعداء الله لنيْل من الدين وتفرقة المسلمين ولازال علماء القرن(21م) ينتهجون هذا النهج، ويتمسكون بالدين ويدعون إليه بالأساليب المختلفة والطرق المواكبة للعصر. فكان للجزائر الحظ الوافر من هؤلاء العلماء الذين هم رجال الدين، الذين حاربوا الجهل والأمية التي سعى الاستعمار إلى نشرها وتفشيها في المجتمع الجزائري، وربوُا أجيال الأمة على النهج السليم، حيث أخذت صحراء الجزائر نصيبًا من هذا الإرث، فظهرت شموعٌ أنارت واحات الصحراء بعلمها ومن بينها الشيخ "" محمد بن سليمان حمداوي"" الذي كان شمسًا ساطعةً في أرض الطيبات بفضل جهوده الجبارة وخدمته للدعوة وتعليم القرآن. الإشكالية: ومن هنا تتبلور إشكالية الدراسة المتمثلة في التساؤل الرئيسي: من هو محمد بن سليمان حمداوي وما الجهود الدعوية التي قدمها؟ و للإجابة عن هذا التساؤل يجب علينا الإجابة على جملة من الإشكاليات الفرعية وهي: 1- كيف كانت البيئة التي عاش فيها الشيخ؟ 2- ما هو نسب الشيخ محمد بن سليمان حمداوي، وأين ولد؟ 3- كيف كان رد فعل أهل الطيبات على الاستعمار؟ 4- فيما تمثلت الحياة العلمية للشيخ؟ 5- ما المجهودات التي قام بها الشيخ في خدمة الإسلام؟ 6- ما هي الآثار التي تركها الشيخ؟ 7- كيف كانت مشاركة الشيخ في الثورة؟ النتائج: بعد هذه الدراسة حول حياة الشيخ ""محمد بن سليمان حمداوي"" وجهوده الدعوية بمنطقة الطيبات وما جاورها من المناطق, وتعليمه للناس ونشره للعلم وإصلاح ذات البين في المنطقة وماجورها, وادي سوف و واد ريغ, توصلنا إلى جملة من النتائج نوردها فما يلي: 1. تعتبر منطقة الطيبات إحدى بلديات ولاية ورقلة, أنشئت بموجب التقسيم الإداري لسنة ""1974م"", التي تقع بين إقليمي وادي ريغ و وادي سوف. 2. تمتاز منطقة الطيبات بمناخ قاري جاف كغيرها من المناطق الصحراوية. 3. ظهرت منطقة الطيبات حسب أغلب الروايات خلال نهاية ""القرن16"" على يد الولي الصالح سيدي محمد بن السائح – رحمة الله عليه-, تشكلت من عروش أهمها : عرش أولاد سيدي محمد بن السائح, عرش أولاد عبد القادر, عرش أولاد جامع. 4. كان لمنطقة الطيبات اسهامات في الثورة من خلال ( معركة الدليليعي و وشوشة العرف و اشتباكات بوخشبة ومظاهرات المنقر). 5. أنجبت منطقة الطيبات ثلة من الأعلام الذين سهروا على نشر العلم وتنوير العقول والنهوض بالقرآن الكريم والسنة المطهرة ونقل الرسالة وأداء الأمانة, من بين هذه الأعلام ""محمد بن سليمان حمداوي"". 6. كان لبيئة الشيخ ""محمد بن سليمان حمداوي"" الاثر الكبير في سقل شخصيته, رغم كل الظروف القاسية التي كانت النقطة الحافزة في تكوين هذه الشخصية الفذة والجبارة التي قامت باحتضان العلم وتوجيهه التوجيه الصحيح لأبناء المنطقة 7. مشاركة الشيخ "" محمد بن سليمان حمداوي"" لنداء الثورة بطريقة غير مباشرة, عن طريق أسلوب الإيحاء في خطبه ودروسه لمساندة الثورة ومد العون . 8. سجن الشيخ "" محمد بن سليمان حمداوي"" سنة ""1960م"" لعلاقته بالقائد حشاني وإلقاء القبض عليه ووضعه داخل الإقامة الجبرية إلى الاستقلال. 9. اشتغل الشيخ "" محمد بن سليمان حمداوي"" إماما. فكان بذلك مفتيا وناصحا وشاعرا ومؤلفا, برغم من العراقيل التي واجهته. 10. الشيخ "" محمد بن سليمان حمداوي"" شخصية رسالية محبة للغير, فقد وهب وقته للإمامة والتدريس والتأليف و تفقه واصلاح ذات البين, وشخصية ثورية من خلال جهاده بالسلوك والقول والفعل للدفاع عل الدين والنهوض به والتصدي للمتعارضين له – قصة النبي مسعود-. 11. كان الشيخ "" محمد بن سليمان حمداوي"" داعيا إلى الله بأساليب خاصة وملائمة لعصره. 12. الشيخ ""محمد بن سليمان حمداوي"" موسوعة علمية ومعرفية من خلال ما تميزت به خطبه وجلساته العلمية الحافلة والراقية وكذا ما ترك من أثار علمية مخطوطة وتأليفه لبعض الكتب التي من بينها كتاب بيان فضل الصلاة النبي  على القرءان وبيان فضل القرءان على الصلاة النبي  تفصيلا لمن فتح الله بصيرته في رسالة قوة الدفاع والهجوم ""The hadith of Abu al-Darda’ The Messenger of God - may God’s prayers and peace be upon him - said: “The scholars are the heirs of the prophets.” Scholars have followed his guidance and followed his trail and followed him, despite all the challenges that the Islamic nation has gone through from wars and conspiracies, and plots orchestrated by the enemies of God to undermine religion and divide Muslims, and scholars of the 21st century (AD) still adopt this approach, cling to religion and call for it in various ways and ways that keep pace with the times. Algeria had the great fortune of these scholars who are the clergy, who fought the ignorance and illiteracy that colonialism sought to spread and spread in the Algerian society, and they raised the generations of the nation on the right path, as the desert of Algeria took a share of this legacy, so candles appeared that illuminated the desert oases with their knowledge and among them Sheikh ""Muhammad bin Suleiman Hamdawi"" who was a shining sun in the land of good things, thanks to his mighty efforts and his service to the call and the teaching of the Qur'an. The problem: From here crystallizes the problem of the study represented in the main question: Who is Muhammad bin Suleiman Hamdawi and what are the advocacy efforts that he presented? In order to answer this question, we must answer a number of sub-problems: 1- How was the environment in which the Sheikh lived? 2- What is the lineage of Sheikh Muhammad bin Suleiman Hamdawi, and where was he born? 3- How did the good people react to colonialism? 4- What was the scientific life of the sheikh represented? 5- What efforts did the Sheikh make in the service of Islam? 6- What are the effects left by the Sheikh? 7- How was the Sheikh's participation in the revolution? Results: After this study on the life of Sheikh ""Mohammed bin Suleiman Hamdawi"" and his advocacy efforts in the Al-Tayebat region and its surrounding areas, teaching people, spreading knowledge and reforming relations in the region and its neighborhoods, Wadi Souf and Wad Rig, we reached a number of results, which we list as follows: 1. The Tayebat region is one of the municipalities of the Wilayat of Ouargla, established according to the administrative division of the year 1974 AD, which is located between the regions of Wadi Rig and Wadi Souf. 2. Al-Tayebat region is characterized by a dry continental climate like other desert regions. 3. According to most narrations, the Al-Tayyibat area appeared at the end of the “16th century” at the hands of the righteous guardian Sidi Muhammad bin Al-Sayeh - may God have mercy on him -. It was formed from the thrones, the most important of which are: the throne of the children of Sidi Muhammad bin Al-Sayeh, the throne of the children of Abdul Qadir, the throne of the children of Jameh. 4. The Al-Tayebat area had contributions to the revolution through (the battle of Al-Dali’i, Wusha Al-Urf, the Boukhashabeh clashes and the Al-Muntqar demonstrations). 5. The Al-Tayebat region gave birth to a group of famous people who were keen on spreading knowledge, enlightening minds, advancing the Noble Qur’an and the purified Sunnah, conveying the message and fulfilling the trust. Among these flags is “Muhammad bin Suleiman Hamdawi”. 6. The environment of Sheikh “Mohammed bin Suleiman Hamdawi” had a great impact on his personality, despite all the harsh circumstances that were the catalyst in the formation of this unique and mighty personality who embraced science and directed it to the right guidance of the people of the region 7. Sheikh ""Mohammed bin Suleiman Hamdawi"" participated in the call of the revolution in an indirect way, through the method of suggestion in his speeches and lessons to support the revolution and extend aid. 8. Sheikh ""Mohammed bin Suleiman Hamdawi"" was imprisoned in 1960 for his relationship with Commander Hachani, arrested and placed under house arrest until independence. 9. Sheikh ""Mohammed bin Suleiman Hamdawi"" worked as an imam. He was a mufti, advisor, poet and author, despite the obstacles he faced. 10. Sheikh “Mohammed bin Suleiman Hamdawi” is a message-loving personality, he devoted his time to leading, teaching, authoring, jurisprudence and reforming the same, and a revolutionary personality through his jihad with behavior, word and deed to defend and advance religion and confront those who oppose it - the story of the Prophet Masoud -. 11. Sheikh ""Mohammed bin Suleiman Hamdawi"" was a caller to God with special methods appropriate to his time. 12. Sheikh “Muhammad bin Suleiman Hamdawi” is a scientific and cognitive encyclopedia through what was distinguished by his speeches and his extensive and refined scientific sessions, as well as what he left from manuscript scientific traces and his authorship of some books, among which is the book Explanation of the Virtue of the Prophet’s Prayer over the Qur’an and Explanation of the Excellence of the Qur’an over Prayer the Prophet ﷺ Detailed for the one who opened his insight in the message of the power of defense and attack"
دعوة واعلام
Keywords: سليمان حمداوي/ الجهود الدعوية / منطقة الطيبات / الدعوة وتعليم القرآن; Suleiman Hamdawi/ Advocacy Efforts/ Al Tayebat/ District/ Dawah and Teaching the Qur’an